2011
DOI: 10.1093/dnares/dsr002
|View full text |Cite
|
Sign up to set email alerts
|

The Complete Chloroplast Genome of 17 Individuals of Pest Species Jacobaea vulgaris: SNPs, Microsatellites and Barcoding Markers for Population and Phylogenetic Studies

Abstract: Invasive individuals from the pest species Jacobaea vulgaris show different allocation patterns in defence and growth compared with native individuals. To examine if these changes are caused by fast evolution, it is necessary to identify native source populations and compare these with invasive populations. For this purpose, we are in need of intraspecific polymorphic markers. We therefore sequenced the complete chloroplast genomes of 12 native and 5 invasive individuals of J. vulgaris with next generation seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
130
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(146 citation statements)
references
References 38 publications
11
130
1
Order By: Relevance
“…Cp SSRs have been used widely in plant population genetics (Doorduin et al, 2011; He et al, 2012), polymorphism investigations (Xue et al, 2012), and ecological and evolutionary studies (Roullier et al, 2011; Wang et al, 2013). The SSRs in the five Juglans Cp genomes we investigated were AT rich.…”
Section: Discussionmentioning
confidence: 99%
“…Cp SSRs have been used widely in plant population genetics (Doorduin et al, 2011; He et al, 2012), polymorphism investigations (Xue et al, 2012), and ecological and evolutionary studies (Roullier et al, 2011; Wang et al, 2013). The SSRs in the five Juglans Cp genomes we investigated were AT rich.…”
Section: Discussionmentioning
confidence: 99%
“…Seven regions (cssA-trnL, psbI-trnS, rpl33-rps18, trnF-ndhJ, trnG-trnT, trnH-psbA, and trnT-trnL) possessed the completely congruent trees with the life history of species. Among them, trnH-psbA has been frequently applied as a phylogenetic maker for Asteraceae family (Doorduin et al 2011), and psbI-trnS has also been Fig. 4 Sequence alignment of eight sequenced cp genomes in the Asteraceae family.…”
Section: Sequence Divergence In Asteraceae Cp Genomes and Marker Idenmentioning
confidence: 99%
“…Although extensive studies have reported the comparative chloroplast genome analysis in many families (Wu et al 2011;Ghimiray and Sharma 2014), a systematic analysis of the structure and organization of chloroplast genomes in Asteraceae family has not been performed up to now. Here, eight chloroplast genomes belonging to different tribes of Asteraceae family are selected as the representative to perform comparative analysis, including Ageratina adenophora (NC_015621) belonging to the tribe Eupatorieae (Nie et al 2012), Artemisia frigida (NC_020607) (Liu et al 2013), Chrysanthemum indicum (NC_020320), and Chrysanthemum × morifolium (NC_020092) all belonging to the tribe Anthemideae, Guizotia abyssinica (NC_010601) (Dempewolf et al 2010) belonging to the tribe Millerieae, Helianthus annuus (NC_007977) (Timme et al 2007) belonging to the tribe Heliantheae and Jacobaea vulgaris (NC_015543) (Doorduin et al 2011) belonging to the Senecioneae clade as well as Lactuca sativa (DQ383816) (Timme et al 2007) belonging to the tribe Lactucinae, with the purpose to compare and analyze the gene content, genome structure, and RNA editing of Asteraceae cp genomes, which will provide helpful information for better understanding of cp genome evolution within this family.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of next-generation sequencing, cp genome-scale data have been increasingly employed to infer phylogenetic relationships at almost any taxonomic levels in the past decade (Jansen et al, 2007; Moore et al, 2007, 2010; Parks et al, 2009; Barrett et al, 2013; Ma P. F. et al, 2014; Carbonell-Caballero et al, 2015; Zhang et al, 2016). In addition, based on comparative genomic analyses, cp genomic hotspots can be identified as DNA barcodes in discriminating species, in terms of informative regions for a specific plant genus, tribe or family (Doorduin et al, 2011; Li et al, 2013, 2014). Our objectives are to: (1) characterize and compare the cp genomes of all six Amana in order to gain insights into their evolutionary patterns; (2) resolve the phylogenetic relationships among all Amana species and among closely related genera; (3) screen and identify the most rapidly evolving DNA regions of the Amana genome for species identification and future phylogeographic studies of the genus.…”
Section: Introductionmentioning
confidence: 99%